Experimental quantification of insect pollination on sunflower yield, reconciling plant and field scale estimates - Perrot, Thomas; Gaba, Sabrina; Roncoroni, Marylin; Gautier, Jean-Luc; Saintilan, Alexis; Bretagnolle, Vincent (Basic and applied ecology, 2019)
Most crops grown in Europe, including sunflower (Helianthus annulus L.), benefit from insect pollination. However, valuing this benefit is not straightforward since estimates of the increase in sunflower yield vary from 18% to 100%. Most estimates have, moreover, been performed at plant scale, a scale that is not relevant for farmers who calculate at the field scale. In this four-year study, we quantified the contribution of insect pollination to sunflower yield at field and plant scales in working farm fields distributed along a gradient of pollinator diversity and abundance. Pollinators were found to increase field yield up to 40% (i.e. 0.7t/ha) and by 31.3% at plant scale; the magnitude of effect on yield being therefore similar at both scales. The pollinators increased the yield by increasing the number of fertilized seeds per plant with no significant effect on the unit mass of the seeds although there was a trade-off between number of seeds and unit mass. Among pollinators, honeybees were the main taxon impacting sunflower yield. Sunflower plant density was a strong determinant of yield, with higher numbers attracting increased numbers of honeybees. Using pollinator and wind exclusion, we finally quantified the relative contributions of self-pollination (∼40%), insect pollination (∼35%) and wind pollination (∼20%). Our results show, to the best of our knowledge, the first evidence of the key role of pollinators in sunflower production at field scale in real farming conditions, and underscore the need to maintain suitable conditions for pollinators in agricultural landscapes.